2007
DOI: 10.1007/s11255-007-9262-2
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders: a systematic review of an emerging major clinical issue in renal patients

Abstract: The prevalence of sleep disorders is significantly higher (up to 80%) in patients with chronic uremia compared to the general population. Sleep disorders appear even in the early stages of chronic kidney disease. These disturbances are complex, including difficulties in falling asleep and awakening, interrupted sleep, nightmares, restless legs syndrome, sleep apnea syndrome, etc. There are still disagreements on the major etiological factors of sleep disorders in the uremic patient. Older age, long dialysis vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
46
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 62 publications
7
46
0
1
Order By: Relevance
“…In our study, we also found that these habits did not contribute to the insomnia severity score. A few studies have suggested that number and severity of comorbidity in hemodialysis patients can be attributed with the increase in the prevalence of sleep disorders [2,4,30]. In our study, we found that ischemic hearth disease was an independent determinant of the insomnia severity score.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In our study, we also found that these habits did not contribute to the insomnia severity score. A few studies have suggested that number and severity of comorbidity in hemodialysis patients can be attributed with the increase in the prevalence of sleep disorders [2,4,30]. In our study, we found that ischemic hearth disease was an independent determinant of the insomnia severity score.…”
Section: Discussionsupporting
confidence: 58%
“…The prevalence of insomnia is greater in dialysis patients than in general population [2,3]. Studies have been reported to range from 45% to 90% [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Problems with sleep are very common in ESRD (up to 40%-80%) and range from insomnia and sleep apnea to restless leg syndrome (31,32). Indeed, poor sleep is itself a predictor of mortality and QOL (33).…”
mentioning
confidence: 99%
“…21 Sleep disorders are closely related to depression both in the general population and HD patients. 9 Disturbed sleep is among the cardinal symptoms of major depression.…”
mentioning
confidence: 99%